Postoperative Urinary Retention Following Laparoscopic Hysterectomy for Benign Gynecologic Diseases - Temtanakitpaisan, Assoc.Prof. Teerayut; Temtanakitpaisan, Assoc.Prof. Amornrat; Buppasiri, Assoc.Prof. Pranom; Salang, Assis. Prof. Lingling; Luanratanakorn, Sanguanchoke (Srinagarind Medical Journal, 2024)
Background and Objective: One of the complications of major gynecological surgical operations is postoperative urine retention (POUR). Urinary retention following a complete laparoscopic hysterectomy (TLH) was much lower than following other types of hysterectomy; therefore, the aim of the study was to determine the incidence of postoperative urinary retention (POUR) following laparoscopic hysterectomy. Methods: This is a descriptive design. One hundred sixty-four women who underwent laparoscopic hysterectomy for benign gynecologic conditions from January 2016 to December 2019. Patient characteristics, indications for hysterectomy, perioperative outcomes, perioperative complications and postoperative complications were recorded. The urinary catheter was removed the day after laparoscopic hysterectomy. Postoperative urinary retention (POUR) is defined as the inability to urinate that requires urinary drainage with straight or indwelling catheterization after the day of surgery. Results: The mean age and body mass index (BMI) were 44.3 + 13.4 years and 24.0 + 4.2 kg/m2, respectively. Thirty-three patients (20.1%) were in postmenopausal, and nine patients (5.5%) had diabetes mellitus. The most common causes of hysterectomy were symptomatic uterine leiomyoma (45.1%), adenomyosis (16.5%), and endometrial hyperplasia (11.0%). Total hysterectomy via a laparoscopic approach was conducted in 152 patients (92.7%). Laparoscopic subtotal hysterectomy was performed in the remaining 12 cases (7.3%). No postoperative urinary retention was detected. Other postoperative complications included postoperative fever (1.8%), surgical site infection (0.6%), urinary tract infection (0.6%) and reoperation (0.6%). Conclusion: The incidence of postoperative urinary retention is very low after laparoscopic hysterectomy in benign gynecologic diseases. In our study, no overt urinary retention was detected. The removal of urinary catheters the day after surgery for laparoscopic hysterectomy patients is safe and suitable.